Included in the list of Top Scientist in the field of Material Science from Research.com - Choulis, Stelios A. (My University, 2026)
Included in the list of Top Scientist in the field of Material Science from Research.com (https://research.com/scientists-rankings/materials-science/cy)
Keywords: Sciences